Epistemic risks in cancer screening: Implications for ethics and policy. (February 2020) - Biddle, Justin B.
Abstract: Cancer screening is the subject of much debate; while screening has the potential to save lives by identifying and treating cancers in early stages, it is also the case that not all cancers cause symptoms, and the diagnosis of these cancers can lead to unnecessary treatments and subsequent side-effects and complications. This paper explores the relationships between epistemic risks in cancer diagnosis and screening, the social organization of medical research and practice, and policy making; it does this by examining 2018 recommendations by the United States Preventative Services Task Force that patients make individualized, autonomy-based decisions about cancer screening on the basis of discussions with their physicians. While the paper focuses on prostate cancer screening, the issues that it raises are relevant to other cancer screening programs, especially breast cancer. The paper argues that prostate cancer screening—and, more generally, the process of risk assessment for prostate cancer—is pervaded by epistemic risks that reflect value judgments and that the pervasiveness of these epistemic risks creates significant and under-explored difficulties for physician-patient communication and the achievement of autonomous patient decision making. Highlights: In 2018, the USPSTF recommended that men make individualized, autonomy-based decisions about prostate cancer screening. Risk assessment for prostate cancer is pervaded by epistemic risks that reflect value judgments. The pervasiveness of these epistemic risks creates under-explored difficulties for physician-patient communication. Autonomous patient decision making will be difficult to achieve without significant organizational changes.